Influenza A Virus Induces Autophagy by Its Hemagglutinin Binding to Cell Surface Heat Shock Protein 90AA1 - Wang, Xingbo; Zheng, Tuyuan; Lin, Lulu; Zhang, Yina; Peng, Xiran; Yan, Yan; Lei, Jing; Zhou, Jiyong; Hu, Boli (Frontiers in Microbiology, 2020)
Autophagy can be utilized by influenza A virus (IAV) to facilitate its replication. However, whether autophagy is induced at the stage of IAV entry is still unclear. Here, we report that IAV induces autophagy by hemagglutinin (HA) binding to heat shock protein 90AA1 (HSP90AA1) distributed on the cell surface. Virus overlay protein binding assay and pull down assay indicated that IAV HA bound directly to cell surface HSP90AA1. Knockdown of HSP90AA1 weakened H1N1 infection. Incubation of IAV viral particles with recombinant HSP90AA1 or prior blockade of A549 cells with anti-HSP90AA1 antibody could inhibit attachment of IAV. Moreover, we found that recombinant HA1 protein binding to cell surface HSP90AA1 was sufficient to induce autophagy through the AKT-MTOR pathway. Our study reveals that the HSP90AA1 on cell surface participates in IAV entry by directing binding to HA1 subunit of IAV and subsequently induces autophagy.